Preservation of C Hexagons in C Allotrope Transformations - Bucknum, Michael J. (2011)
In this Letter is described the analogous hexagon preserving C allotrope transformations of graphite to diamond, as a packing of C spheres on the one hand, and alternatively C nanotubes to the C allotrope hexagonite, as a packing of C cylinders on the other hand.